التلوث البصري في مدينة الناصرية - ضيف الله تيسير علي عبد الواحد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Visual pollution within urban areas is considered one of the primary obstacles affecting the process of urban development. Studying these pollutants, along with identifying their causes and manifestations, has become essential in order to arrive at effective solutions that mitigate their health and psychological impacts on residents. The main objective of this research is to uncover the causes and forms of visual pollution in the study area. The findings highlight the most significant manifestations of visual pollution in the city of Nasiriyah, which result from traffic congestion, informal housing, solid waste, and buildings under construction. The research addresses visual pollution, its underlying causes, and its observable forms, while also presenting conclusions and recommendations.